From Pedagogy to Educational Science: Inspired By Meile (Love) - Jucevičienė, Palmira (Pedagogika, 2013)
Education is sociocultural phenomenon which has significantly influenced the development of the society and also is under the development itself. The complexity of changes experienced by the society generates the challenges for the educational practice and theory. Respectfully – conditioning the needs for the development of the body of knowledge necessary for education and its production. Regaining independence of Lithuania in 1990 opened up new opportunities for educational practice and research in the country. Dr. Meile Luksiene’s works on the Concept of National School inspired researchers and practitioners for educational reform which invited to search for new knowledge in the area of education. Pedagogy, as traditional discipline by itself, researching only the educational process, not the system of education and lifelong learning, was no longer sufficient. Interdisciplinary and most importantly multidisciplinary approaches towards the reality and perspectives of education were necessary. The aim of this article is to reveal the road of the scientific discipline development in Lithuania from pedagogy to educational science on the foundation of both national and world wide trends which have been consistently influencing this development.